AI UNTUK GENERASI CERDAS: BELAJAR TEKNOLOGI BERSAMA PENDIDIKAN PROFESI GURU - Abdul Wafi; Adi Wahyu Wardani; Ainun Nur Baiti; Dwi Widiyasari; Ella Amelia Widodo; Moh. Nur Zamzami; M. Ajie Kalifatullah; Khoirul Anwar; Sigit Perdana; Azhar Ahmad Smaragdina; Didik Dwi Prasetya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The advancement of artificial intelligence (AI) technology presents both challenges and opportunities in the field of education. This report presents the outcomes of a community service activity conducted by lecturers and student-teachers from the Teacher Professional Education (PPG) Program at Universitas Negeri Malang through an educational talk show at SMA Negeri 8 Malang. The initiative aimed to improve digital literacy among students and teachers regarding the ethical and responsible use of AI. The talk show involved students, teachers, and student council members (OSIS), and featured expert speakers who discussed the fundamentals of AI, its applications, and associated risks such as technological dependency and academic plagiarism. The activity led to increased awareness of the benefits and challenges of AI, as well as the importance of academic integrity and character in its use. The school responded positively by establishing an AI Literacy Team, organizing teacher workshops, and launching the campaign “Smart AI, Not Instant AI.” This program serves as a model for promoting an adaptive and ethical digital culture within secondary education.